PAI INTRAKURIKULER LEARNING BASED ON FREEDOM OF LEARNING AT THE DRIVING SCHOOL OF SMA NEGERI 2 BATU - Rofiq, Ahmad Ainur; Ali, M. Makhrus; Maulidi, M. Hilal; Mahbuubah, Nabiilatul (Universitas Yudharta Pasuruan, 2025)
Intracurricular learning is one of three types of learning offered in the independent curriculum. This learning activity is implemented during the lesson hours that have been regulated in the curriculum. This intracurricular learning activity emphasizes the knowledge and academic competencies needed by students. Intracurricular learning of Islamic Religious Education at SMA Negeri 2 Kota Batu is carried out using differentiated learning where educators are given the freedom to design learning that suits the characteristics of students at SMA Negeri 2 Kota Batu. In intracurricular learning, educators act as facilitators for students who have different abilities, different learning styles and also differences in appreciating the understanding of what has been learned in intracurricular learning. This research was carried out at the driving school SMA Negeri 2 Batu City using a qualitative approach. This type of research is a case study. The aim of this research is to find out the procedures for implementing PAI intracurricular learning at SMA Negeri 2 Batu City. The results of this research are that there are 7 stages of planning and PAI intracurricular learning is carried out with differentiated learning. the evaluation process for PAI intracurricular learning is carried out with summative and formative assessments.